2015
DOI: 10.1007/s12039-015-0982-z
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the structure of SARS 3a transmembrane protein using a minimum unfavorable contact approach

Abstract: 3a is an accessory protein from SARS coronavirus that is known to play a significant role in the proliferation of the virus by forming tetrameric ion channels. Although the monomeric units are known to consist of three transmembrane (TM) domains, there are no solved structures available for the complete monomer. The present study proposes a structural model for the transmembrane region of the monomer by employing our previously tested approach, which predicts potential orientations of TM α-helices by minimizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…CoV2 is critical for 3DB formation 3a CoV2 and 3a CoV1 share a similar domain structure: an N-terminal region (N-term), a transmembrane-domain region (TMD) and a C-terminal region (C-term) 14,41 , with ~72% amino acid (aa) identity (Fig. 3a).…”
Section: The C-terminal Region Of 3amentioning
confidence: 99%
“…CoV2 is critical for 3DB formation 3a CoV2 and 3a CoV1 share a similar domain structure: an N-terminal region (N-term), a transmembrane-domain region (TMD) and a C-terminal region (C-term) 14,41 , with ~72% amino acid (aa) identity (Fig. 3a).…”
Section: The C-terminal Region Of 3amentioning
confidence: 99%
“…Unlike water-soluble proteins, hydrophobic residues of membrane proteins are exposed towards the membrane instead of being buried in the protein interior. Conversely, hydrophilic residues can reside on the protein surface, outside the membrane, neighboring the lipid headgroups, even sometimes, in the protein interior, for example, while forming a channel (Harris and Booth 2012;Ramakrishna et al 2015;Padhi et al 2015). Recent advances in experimental structural biology and computer simulation methodologies have facilitated our understanding on the structural and functional bases of membrane channels at atomic resolution.…”
Section: Urea Conduction Through Membrane Proteinsmentioning
confidence: 99%
“…NMR studies on the monomeric form have shown that the protein is predominantly α-helical, with two transmembrane segments being connected by a loop. Due to the difficulty in obtaining transmembrane protein structure, several computational methodologies have been proposed. There have been a number of attempts to computationally model the oligomeric structure of the p7 protein. The first complete oligomeric structure was reported in an electron microscopy study, which revealed a flower-shaped structure of the channel . Such a shape of the channel was later confirmed in an NMR study, which showed a hexamer with a funnel-shaped pore. , Each monomeric unit possesses three α-helices, and the different monomeric units are intertwined with one another.…”
Section: Introductionmentioning
confidence: 99%